2021
DOI: 10.1155/2021/4132488
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Enhances Activity and Malignant Behaviors of Colorectal Cancer Cells through the STAT3/MicroRNA-19a/PTEN/PI3K/AKT Axis

Abstract: Hypoxia is a typical microenvironment feature in almost all solid tumors and is frequently associated with growth of cancers including colorectal cancer (CRC). This study focuses on the influence of hypoxic microenvironment on the activity of CRC cells and the molecules involved. CRC cells were cultured under hypoxic conditions for 48 h, after which the proliferation, migration, invasion, and epithelial-mesenchymal transition activities of cells were increased. MicroRNA- (miR-) 19a was significantly upregulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…STAT3 transcription factor binds to a region 96 bp/78 bp upstream of miR-19a within its promoter, leading to the induced expression of this oncogenic miRNA. The overexpression of miR-19a was shown to downregulate PTEN mRNA expression, promote cell viability and EMT in CRC cells, and increase tumor growth and metastasis in nude mice models through STAT3/miR-19a/PTEN axis [ 94 ]. Moreover, STAT3 has been illustrated to induce the expression of miR-181b as an oncomiR in CRC cells.…”
Section: Stat3 Upregulates or Downregulates Mirnasmentioning
confidence: 99%
“…STAT3 transcription factor binds to a region 96 bp/78 bp upstream of miR-19a within its promoter, leading to the induced expression of this oncogenic miRNA. The overexpression of miR-19a was shown to downregulate PTEN mRNA expression, promote cell viability and EMT in CRC cells, and increase tumor growth and metastasis in nude mice models through STAT3/miR-19a/PTEN axis [ 94 ]. Moreover, STAT3 has been illustrated to induce the expression of miR-181b as an oncomiR in CRC cells.…”
Section: Stat3 Upregulates or Downregulates Mirnasmentioning
confidence: 99%
“…HIF is closely associated with chemoresistance by activating the β-catenin/Wnt signaling pathway maintaining tumor cell stemness [ 109 ]. Tang et al [ 110 ] revealed that a hypoxic culture environment promotes STAT3 phosphorylation in CRC cells and promotes tumor progression through PI3K/AKT pathway activation.…”
Section: Tme and Chemotherapy Obstaclesmentioning
confidence: 99%
“…These nine factors occupy important positions in the large regulatory network of the body (22)(23)(24)(25)(26)(27). Changing of their expression may lead to changes or even loss of control of the regulatory network (22,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). In addition, these factors are highly related to the development and growth, regulatory mechanisms and microenvironment maintenance of early embryos (4,6,17,30,(38)(39)(40)(41)(42).…”
Section: Expression Level Comparison Of Marker Genes Related To Early...mentioning
confidence: 99%
“…In addition, these factors are highly related to the development and growth, regulatory mechanisms and microenvironment maintenance of early embryos (4,6,17,30,(38)(39)(40)(41)(42). MYC (29,31,43), MYB (26), BCL-2 (44)(45)(46), BNIP3 (47), p53 (27,48), PI3K (22,28), AKT (23,49) and mTOR (32,(50)(51)(52)(53) are regarded as proto-oncogenes that serve important roles in cell proliferation and differentiation, apoptosis, cell cycle regulation and metabolic processes. In previous studies of mouse embryonic development, high mRNA and protein expression levels of these proto-oncogenes were also detected in mouse embryos.…”
Section: Expression Level Comparison Of Marker Genes Related To Early...mentioning
confidence: 99%